Principles of small business management - Hatten, Timothy S. (South-Western/Cengage Learning, 2012)
Provides an introduction to both entrepreneurship and small business management with a focus on achieving and maintaining a sustainable competitive advantage as a small organization. This title highlights issues including global opportunities, service, quality and technology.